Prevalence, Incidence, and Characteristics of Adverse Drug Reactions Among Older Adults Hospitalized at Mbarara Regional Referral Hospital, Uganda: A Prospective Cohort Study - Yadesa, Tadele Mekuriya; Kitutu, Freddy Eric; Tamukong, Robert; Alele, Paul E (Clinical Interventions in Aging, 2021)
Background: Adverse drug reactions (ADRs) are associated with significant clinical and economic effects. Among the elderly population, the risk for ADRs is even higher. Data of ADR prevalence and incidence among the elderly population in Uganda and many low- and middle-income countries are lacking. Objective: This study determined the prevalence, incidence, and characteristics of ADRs among hospitalized elderly patients at Mbarara Regional Referral Hospital (MRRH), Uganda. Methods and Materials: We conducted a prospective cohort of older adults admitted to medical, oncology, and surgery wards at MRRH for consecutive 6 months. The primary data were obtained by interviewing patients and caregivers and reviewing patient medication charts, taking vital signs, and physical examinations. We used Edwards and Aronson’s definition of ADR and the Naranjo ADR Causality Scale. We conducted descriptive statistics and the Kolmogorov–Smirnov test using SPSS Version 23.0. Results: We studied a total of 523 older adults 60 to 103 years of age. During their hospital stay, 256 (48.9%) of the patients experienced at least one ADR. A total of 365 ADRs were identified during 4702 person-days of follow-up. The incidence of ADRs was 78 ADRs/ 1000 person-days. ADRs affecting the gastrointestinal tract were the most frequently (40.6%) identified categories. Probable and type A ADRs accounted for 260 (71.2%) and 305 (83.6%) of the total incidents, respectively. Overall, 237 (64.9%) of the ADRs were rated as mild, whereas 10 (2.8%) of them as severe. Lastly, 165 (45.2%) of the ADRs were categorized as preventable. Conclusion: Almost half of the hospitalized patients aged 60 to 103 years experienced at least one ADR during their hospital stay, which is higher than has been previously documented. Almost three-thirds of the ADRs were probable, about 4 out of 5 were type A and almost two-thirds were mild. Nearly half of the ADRs were preventable.
Keywords: Prevalence; Incidence; Mechanism; Severity; Preventability; Adverse drug reaction; Elderly; Inpatients